2006
DOI: 10.1111/j.1365-2141.2006.06108.x
|View full text |Cite
|
Sign up to set email alerts
|

Safe adoptive transfer of virus‐specific T‐cell immunity for the treatment of systemic adenovirus infection after allogeneic stem cell transplantation

Abstract: SummaryDuring periods of immunosuppression, such as postallogeneic stem cell transplantation (SCT), patients are at significant risk for severe viral infections. Human adenovirus (HAdV) infection is a serious complication post‐SCT, especially in children. Virus‐specific T cells are essential for the clearance of HAdV, as antiviral chemotherapy has revealed limited success. We present feasibility data for a new treatment option using virus‐specific donor T cells for adoptive transfer of immunity to patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
309
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 365 publications
(318 citation statements)
references
References 41 publications
8
309
0
1
Order By: Relevance
“…This strategy has been successfully used in patients with CMV disease or viremia, with a response rate of 83%, 90 EBV, with a response rate of 50-70% 91,92 and ADV, with responses in 5 of 6 patients in a small study. 93 Adoptive transfer of VSTs from an adult stem cell donor is effective as prophylaxis and treatment for treatment-refractory EBV, CMV and ADV infections. 83,84 However, there are considerable barriers to successful use of adoptive immunotherapy with VSTs post-UCBT; specifically, there are small numbers of T-cells available for manipulation and their phenotype is naïve.…”
Section: Infectionmentioning
confidence: 99%
“…This strategy has been successfully used in patients with CMV disease or viremia, with a response rate of 83%, 90 EBV, with a response rate of 50-70% 91,92 and ADV, with responses in 5 of 6 patients in a small study. 93 Adoptive transfer of VSTs from an adult stem cell donor is effective as prophylaxis and treatment for treatment-refractory EBV, CMV and ADV infections. 83,84 However, there are considerable barriers to successful use of adoptive immunotherapy with VSTs post-UCBT; specifically, there are small numbers of T-cells available for manipulation and their phenotype is naïve.…”
Section: Infectionmentioning
confidence: 99%
“…49,50 An algorithm for treatment of ADV infections has been reviewed in detail by Feuchtinger et al 51 Low numbers of specific T cells were isolated after ex vivo stimulation by IFN-g secretion and magnetic microbeads and administered without inducing GVHD. 52 Outcome and future perspectives Transplant related mortality could be effectively reduced by improved T cell recovery and close monitoring of viral loads followed by preemptive therapy and by the use of reduced-intensity conditionings, whereas relapse remains the major cause of death. 53 3y-EFS in single center studies with CD34 þ selected grafts were 36 and 48% for ALL (CR1-3) and 18 and 28% for myeloic leukemias (CR1-2); 11,13 a recent collaborative retrospective study showed 3y-EFS of 35% (CR1), 28% (CR2) and 0% (CR3) in patients with ALL.…”
Section: Immune Reconstitution and Trmmentioning
confidence: 99%
“…16 For this reason, immunotherapy with donor T cells has been suggested, and a novel approach using purified AdV-specific donor T cells is promising, although in need of further evaluation. 17 At present, surveillance of AdV infection after HSCT is not routinely implemented, although the technology of choice, quantitative PCR, is widely available. The possible advantages are that such surveillance programs facilitate early detection and intervention and promote preemptive treatment before symptoms emerge.…”
Section: Introductionmentioning
confidence: 99%